Prospective Longitudinal Study of Gait and Balance in a Cohort of Elderly Essential Tremor Patients - Dowd, Hollie; Zdrodowska, Maria Anna; Radler, Keith H.; Cersonsky, Tess E. K.; Rao, Ashwini K.; Huey, Edward D.; Cosentino, Stephanie; Louis, Elan D. (Frontiers in Neurology, 2020)
Background: Essential tremor (ET) encompasses a variety of features, including tremor, cognitive dysfunction, and gait and balance impairments. Gait and balance impairments in ET are often mild, but they can be severe and are, in some cases, associated with functional sequelae in terms of increased fall risk and reduced balance confidence. Previous research on gait and balance in ET has been limited to cross-sectional comparisons. There have been no longitudinal studies or prospective studies. As such, our understanding of natural history and possible predictors of declines in ET-related gait and balance impairments is incomplete. Objectives: We (1) present natural history data on the change in gait and balance measures over time, (2) provide estimates of annual rate of change in each gait and balance metric, and (3) examine the relationship between baseline clinical predictors and changes in gait and balance over time. Methods: 149 ET participants (mean age 78.7 years), enrolled in a prospective, longitudinal, clinical-pathological study, underwent an extensive evaluation of cognition, tremor, and gait and balance at three distinct intervals performed every 18 months. Gait and balance measures included a combination of performance-based tests (e.g., tandem gait, tandem stance) and self-reported assessments (e.g., number of falls, use of a walking aid). Results: Between the baseline and final assessments, numerous balance and gait measures showed evidence of decline and annual rates of change were quantified for each. We examined the predictive utility of clinical variables at baseline for five gait and balance outcomes, with global cognition and executive function standing out as the most consistent predictors. Conclusions: We present a much-needed look into the course of disease for elderly patients with ET, focusing on changes observed in gait and balance and the predictors of these changes. These results also add another dimension to the relevance of cognitive impairment observed in ET; such impairment can now be viewed as predictive of poorer gait and balance over time in ET. These findings are a useful tool for clinicians, patients, and their families to better understand and plan for changing disease-features over time.